Paradoks Negara Hukum: Refleksi Kritis atas Dialektika Wacana dan Realitas Pemberantasan Korupsi di Indonesia - Pawe, Taufan; Husen, La Ode; Muzakkir, Abd. Kahar (CV. Social Politic Genius (SIGn), 2025)
Although Indonesia is constitutionally a rule-of-law state as enshrined in Article 1(3) of the 1945 Constitution, the persistence of systemic corrupt practices, as reflected in the stagnant Corruption Perception Index score, indicates a fundamental paradox. This article aims to conduct an in-depth critical analysis of this paradox by dissecting the dialectic between the normative anti-corruption discourse and the realities of political pragmatism and socio-cultural logic. Employing a normative legal research method enriched by an interdisciplinary approach—encompassing constitutional philosophy, political law, and the sociology of law—this study analyzes legal products such as Law Number 31 of 1999 and Law Number 30 of 2002 as manifestations of the existing tension. The analysis reveals that contesting interests in the legislative and political process has produced a normative ambivalence. This ambivalence, in turn, leads to neutralizing the effectiveness of Law Number 31 of 1999 when it confronts socio-cultural realities, thereby creating a systemic law enforcement anomaly. In conclusion, the resolution to this paradox demands a reconstruction of the meaning of a rule of law state transcending juridical formalism, requiring a progressive synthesis that revitalizes the spirit of substantive justice within the constitution as the foundation for all policy and law enforcement.